Action research in a problem avoiding culture using a Buddhist systems methodology. Issue 2 (June 2015) - Shen, Chao-Ying; Midgley, Gerald
Problem avoidance can be an issue in both Eastern and Western cultures, and in some Eastern contexts it can stem from the desire to promote organizational harmony: identifying problems can lead to blame, thereby fracturing harmonious relationships. The authors have developed and applied a Buddhist systems methodology (BSM) to counteract problem avoidance in Taiwanese Buddhist organizations. Unlike many Western action research approaches, which require participants to start by identifying problems or problematic situations, the BSM uses Buddhist concepts that are closely associated with the practice of harmonious living. Thus, it reframes problem exploration as the exercise of Buddhist discipline applied to organizational life, which is likely to be viewed as a co-operative and culturally valued endeavour. In a project with a large non-profit organization, the authors tackled a significant conflict and underlying issues. An evaluation of the project demonstrated that the BSM helped overcome the culture of problem avoidance. While the BSM itself might only be relevant to Buddhist organizations, there is a wider principle at work: when problem avoidance has cultural roots, action researchers could usefully look at how problem exploration might be reframed using a way of thinking that is culturally familiar and highly valued by the participants.